PENGARUH PENGGUNAAN MEDIA VIDEO ANIMASI TERHADAP HASIL BELAJAR MATEMATIKA SISWA PADA MATERI NILAI TEMPAT BILANGAN KELAS II SDN 05 PULAU PUNJUNG - Ratnawati; Dhara atika putri; Futri Hariyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the persistently low student learning outcomes and the limited use of animated video media in instruction. The study aimed to determine the effect of using animated video media on the Mathematics learning outcomes of second-grade students at SDN 05 Pulau Punjung regarding the topic of place value. An experimental method employing a One-Group Pretest-Posttest design was used. The research subjects consisted of 25 second-grade students from SDN 05 Pulau Punjung. Data collection involved learning outcome tests in the form of a pretest and a posttest. Data analysis utilized descriptive and inferential statistics, specifically the Shapiro-Wilk normality test and the Paired Sample t-test, performed using SPSS software. The results showed that the mean pretest score was 43.76, while the mean posttest score was 73.28, representing an increase of 29.52 points. Normality test results indicated that both pretest and posttest data were normally distributed, with significance values ​​of 0.306 and 0.800, respectively (>0.05). Furthermore, the Paired Sample t-test yielded a significance value (Sig. 2-tailed) of 0.000 (<0.05); consequently, the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ) was accepted. Thus, it can be concluded that the use of animated video media has a positive and significant effect on the Mathematics learning outcomes of second-grade students at SDN 05 Pulau Punjung regarding the topic of place value. Animated video media enhances conceptual understanding, attention, motivation, and learning outcomes, making it a suitable alternative instructional medium for Mathematics in primary schools.